Antenatal Dexamethasone for Early Preterm Birth in Low-resource Countries. Issue 3 (25th September 2021) - Oladapo, O.T.; Vogel, J.P.; Piaggio, G.; Nguyen, M.H.; Althabe, F.; Gülmezoglu, A.M.; Bahl, R.; Rao, S.P.N.; De Costa, A.; Gupta, S.; Baqui, A.H.; Khanam, R.; et al.
Abstract : ( N Engl J Med . 2020;383:2514–2525) Antenatal glucocorticoids are a common intervention in preventing adverse outcomes associated with preterm birth. The evidence supporting this intervention is based on trials in high-resource settings, however, and a 2015 trial in low-resource countries found scaling up this intervention caused an increase in neonatal death, stillbirth and suspected maternal infection. The World Health Organization (WHO) has issued guidelines restricting the use of antenatal glucocorticoids to certain situations. This study, the WHO ACTION-1 (Antenatal Corticosteroids for Improving Outcomes in Preterm Newborns) trial, aimed to determine the levels of safety and efficacy of dexamethasone in women at risk for early preterm birth in low-resource countries compared with placebo.